Plants with silver nanoparticles to improve electrical conductivity: an innovative approach in biology - M. Merino-Treviño; A. B. Morales-Cepeda; H. Peraza-Vázquez; E. Onofre-Bustamante (International Journal of Environmental Science and Technology, 2025)
This paper shows the effect of electrical conductivity on the vascular system of plants through the utilization of silver nanoparticles supported by nanocellulose. The plant Epipremnum aureum , also known as pothos, was used in the experimentation. The main characteristics of the plant are its vigorous growth, remarkable adaptability to thrive in both soil and aquatic environments, simple propagation, and noteworthy resilience against diseases. The experiment used a polarization voltage ranging from − 1.5 to 1.5 V and shunt resistors of 1, 10, 100, and 1000 ohms. The scan polarization rate was 15 mV/s. Methods like environmental scanning electron microscopy and energy-dispersive X-ray analysis were used for chemical and structural analysis. The findings demonstrate that adding silver nanoparticles held together by nanocellulose enhances the vascular system's capacity to conduct electricity. Moreover, the Wilcoxon signed-rank test results revealed no statistically significant difference between the root-steam and stem-leaf output voltage values. These findings imply that silver nanoparticles are distributed throughout the vascular system and act as conductive pathways in plants. Additionally, electrolysis-Faraday's law was used to calculate the recovery of silver material, yielding 40 mg/mm 2 per hour. These discoveries open new avenues for comprehending and manipulating plant physiological processes, potentially leading to beneficial outcomes in agriculture and contaminant recovery.